Apokaliptiek by Qumran (1 QS en 1 QH) - Steyn, J. G. L.(Johannes Gerhardus Lombard),1967- (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Litt. et Phil.) -- Universiteit van Stellenbosch, 1994.